A study on the formation of the nitro radical anion by ornidazole and its significant decrease in a structurally characterized binuclear Cu(II)-complex: impact in biology. Issue 4 (11th December 2014) - Santra, Ramesh Chandra; Ganguly, Durba; Singh, Jyotsna; Mukhopadhyay, Kasturi; Das, Saurabh
Abstract : An acetate-bridged binuclear Cu (II) complex of the antiparasitic drug ornidazole is able to decrease the formation of the nitro radical anion. Abstract : An acetate-bridged binuclear Cu (II) complex of the antiparasitic drug ornidazole was synthesized and characterized by different techniques. Single crystal X-ray diffraction revealed that the complex had a paddle wheel structure. Enzymatic assay experiments performed under anaerobic conditions on ornidazole and its Cu (II) -complex using xanthine oxidase as a model nitro-reductase showed that complex formation is able to cause a significant decrease in the reduction of the nitro group on the imidazole ring. Reduction products of 5-nitroimidazoles interact with DNA, causing destruction of the double helical structure and strands, leading to the inhibition of protein synthesis. Although not directly coordinated to the metal center, such a decrease in the generation of nitro radical anion through complex formation would result in decreased cytotoxicity of the complex, which could be a disadvantage from the standpoint of drug efficacy. For this reason, other aspects associated with the drug action of 5-nitroimidazoles, such as DNA binding, were studied. Experiments using cyclic voltammetry revealed that the binding of the complex was almost comparable to ornidazole. Bactericidal activity of ornidazole and the complex was studied on two separate bacterial strains, showing that the complex was comparable to ornidazole. Nitro radical anions are known to adversely affect the central nervous system, and this study showed that the Cu (II) complex has the ability to decrease the generation of NO2 ˙ − to an extent that struck the correct balance for beneficial activity, as cytotoxicity due to ornidazole was not affected.